Trehalose Polyphleates, External Cell Wall Lipids in Mycobacterium abscessus, Are Associated with the Formation of Clumps with Cording Morphology, Which Have Been Associated with Virulence - Llorens-Fons, Marta; Pérez-Trujillo, Míriam; Julián, Esther; Brambilla, Cecilia; Alcaide, Fernando; Byrd, Thomas F.; Luquin, Marina (Frontiers in Microbiology, 2017)
Mycobacterium abscessus is a reemerging pathogen that causes pulmonary diseases similar to tuberculosis, which is caused by Mycobacterium tuberculosis. When grown in agar medium, M. abscessus strains generate rough (R) or smooth colonies (S). R morphotypes are more virulent than S morphotypes. In searching for the virulence factors responsible for this difference, R morphotypes have been found to form large aggregates (clumps) that, after being phagocytosed, result in macrophage death. Furthermore, the aggregates released to the extracellular space by damaged macrophages grow, forming unphagocytosable structures that resemble cords. In contrast, bacilli of the S morphotype, which do not form aggregates, do not damage macrophages after phagocytosis and do not form cords. Cording has also been related to the virulence of M. tuberculosis. In this species, the presence of mycolic acids and surface-exposed cell wall lipids has been correlated with the formation of cords. The objective of this work was to study the roles of the surface-exposed cell wall lipids and mycolic acids in the formation of cords in M. abscessus. A comparative study of the pattern and structure of mycolic acids was performed on R (cording) and S (non-cording) morphotypes derived from the same parent strains, and no differences were observed between morphotypes. Furthermore, cords formed by R morphotypes were disrupted with petroleum ether (PE), and the extracted lipids were analyzed by thin layer chromatography, nuclear magnetic resonance spectroscopy and mass spectrometry. Substantial amounts of trehalose polyphleates (TPP) were recovered as major lipids from PE extracts, and images obtained by transmission electron microscopy suggested that these lipids are localized to the external surfaces of cords and R bacilli. The structure of M. abscessus TPP was revealed to be similar to those previously described in Mycobacterium smegmatis. Although the exact role of TPP is unknown, our results demonstrated that TPP are not toxic by themselves and have a function in the formation of clumps and cords in M. abscessus, thus playing an important role in the pathogenesis of this species.